Heart Transplantation in Congenital Heart Disease: In Whom to Consider and When?. (7th February 2013) - Attenhofer Jost, Christine H.; Schmidt, Dörthe; Huebler, Michael; Balmer, Christian; Noll, Georg; Caduff, Rosmarie; Greutmann, Matthias
Abstract : Due to impressive improvements in surgical repair options, even patients with complex congenital heart disease (CHD) may survive into adulthood and have a high risk of end-stage heart failure. Thus, the number of patients with CHD needing heart transplantation (HTx) has been increasing in the last decades. This paper summarizes the changing etiology of causes of death in heart failure in CHD. The main reasons, contraindications, and risks of heart transplantation in CHD are discussed and underlined with three case vignettes. Compared to HTx in acquired heart disease, HTx in CHD has an increased risk of perioperative death and rejection. However, outcome of HTx for complex CHD has improved over the past 20 years. Additionally, mechanical support options might decrease the waiting list mortality in the future. The number of patients needing heart-lung transplantation (especially for Eisenmenger's syndrome) has decreased in the last years. Lung transplantation with intracardiac repair of a cardiac defect is another possibility especially for patients with interatrial shunts. Overall, HTx will remain an important treatment option for CHD in the near future.